Post-Mortem analyses of Oryctolagus cuniculus acutely poisoned with potassium cyanide and dichlorvos (sniper)ER®) - Iroanya, Onyekachi; Egwuatu, Tochukwu; Ekwedike, Chinenye (Journal of Current Biomedical Research, 2022)
Acute poisoning with toxic substances such as Dichlorvos (Sniper®) and Potassium Cyanide (KCN) has become a threat to human life especially in Nigeria where there have been increased cases of suicidal poisoning in recent times. This study aimed to ascertain the Post-mortem analyses of Oryctolagus cuniculus acutely poisoned with potassium cyanide and dichlorvos (Sniper®). Eighteen rabbits were used for histopathologic, haematologic, biochemical and molecular changes induced by acute oral KCN and Sniper® poisoning for a period of 21 days. The decomposition process was monitored and muscle tissue were sampled for DNA integrity and microbial assays.